Pemberdayaan Masyarakat dengan CKG dan Terapi Akupunktur untuk Nyeri Muskuloskeletal - Sholichan Badri; Nurtama Aditya Nugraha (Health Care : Journal of Community Service, 2025)
This community service activity aimed to improve knowledge and provide acupuncture therapy as a non-pharmacological intervention for musculoskeletal pain among adults and elderly residents in Gumulan Village. Musculoskeletal pain is a common health issue associated with physical activity, occupation, and aging. The methods included health education, basic health screening, and acupuncture therapy. Fifty residents participated in health screening, revealing that 25% had hypertension, 15% had elevated cholesterol, and 9% had high blood glucose. Twenty-four residents received acupuncture therapy, predominantly for low back pain, knee pain, shoulder pain, headaches, and sleep disturbances. The program improved participants’ understanding and provided safe complementary therapy. Overall, the activity was beneficial and recommended for continuation.